The Influence of Economic Factors, Access to Health Services, and Social Support on Drug Abuse Prevention and Treatment Efforts in Urban Communities in East Java - Siti Aisyah; Heni Widyaningsih; Iwan Harsono; Dito Anurogo; Sulistyo Andarmoyo (Westscience Press, 2024)
The dynamics of drug addiction prevention and treatment initiatives in East Java, Indonesia's metropolitan neighborhoods are examined in this study. The study uses structural equation modeling to examine the connections between economic circumstances, social support, health service accessibility, and efforts for drug misuse prevention and treatment, utilizing a sample of 140 people. Strong validity and reliability are demonstrated by the measurement methodology, confirming the effectiveness of the chosen indicators. The results of the structural model demonstrate complex relationships: social support emerges as a key component, although economic variables and health services show favorable links. The study's recommendations for multimodal interventions that tackle economic inequality, improve healthcare accessibility, and bolster community-based initiatives have consequences for both policy and practice. Despite its limitations, this study provides important new understandings of the intricate field of drug misuse intervention treatments and paves the way for more research.